Аналіз електродних систем та конструкцій апаратів для очищення олій в електричному полі - Назаренко, Ігор Петрович; Назаренко, Игорь Петрович; Nazarenko, Ihor; Кушлик, Роман Васильович; Кушлык, Роман Васильевич; Kushlyk, Roman; Кушлик, Руслан Романович; Кушлык, Руслан Романович; Kushlyk, Ruslan; Стручаєв, Микола Іванович; Стручаев, Николай Иванович; Struchaiev, Mykola (My University, 2021)
UK: В роботі проведено аналіз найбільш поширених електродних систем та конструкцій апаратів з вертикальними та горизонтальними електродами, дискових і стрічкових електроосаджувачів, електроосаджувачів з циліндричними і барабанними електродами, шнековими електроосаджувачами, та коронного електросепаратора для очищення олії в електричному полі. Електроосаджувачі з вертикальними та горизонтальними електродами в процесі роботи потребують періодичної промивки електродної системи, що є їх недоліком. До електроосаджувачів з пластинчастими електродами належать дискові та стрічкові електроосаджувачі. Загальним недоліком електроочищувачів з пластинчастими електродами є можливість видалення тільки таких частинок домішок, які мають заряд, до того ж, тільки певного знаку. До істотних недоліків барабанного апарату слід віднести малу площу поверхні осаджувального електроду. Шнекові осаджувачі мають добре організований процес очищення рідини, проте основним недоліком є порівняно мала поверхня електродів. Електродні системи коронного розряду дозволяють отримати потік іонів в газовому середовищі проте основним недоліком є складність конструкції. EN: The analysis of the most common electrode systems and designs of devices with vertical and horizontal electrodes, disk and belt electrodepositors, electrodepositors with cylindrical and drum electrodes, screw electrodepositors, and corona electroseparator for oil purification in electric field. Electric precipitators with vertical and horizontal electrodes allow the coagulation of particles of concentrated suspensions in an alternating electric field. In the process, such devices require periodic flushing of the electrode system, which is their disadvantage. Plate electrode precipitators include disc and tape precipitators. Their advantage is the counter-movement of the suspension and sediment on the belt or disk, which allows you to use them for fine cleaning of the liquid. A common disadvantage of electric cleaners with plate electrodes is the ability to remove only those particles of impurities that have a charge, in addition, only a certain sign that limits their use. Unlike precipitators with cylindrical electrodes arranged coaxially, in the drum precipitator the process is better organized. The precipitate with the electrode moves towards the flow of the suspension, so the liquid as it is cleaned gets into cleaner areas. In principle, at the outlet of the liquid from the device, the electrodes can be completely clean. The precipitate is removed from the liquid into the gas space and is removed from the drum. Part of the liquid at the exit of the precipitate into the gaseous medium flows back into the bath. This reduces the loss of the product to be cleaned. The design of the drum electric precipitator is relatively simple, its operation is reliable. Significant disadvantages of the drum apparatus include the small surface area of the precipitating electrode and the presence of the liquid-gas interface, and with cylindrical electrodes in continuous apparatus complicated problem is the unloading of sediment. Screw precipitators have a well-organized liquid purification process, but the main disadvantage is the relatively small surface of the electrodes and the complexity of the design of moving parts, due to the need for their electrical insulation. Coron discharge electrode systems allow to obtain the flow of ions in a gaseous medium, but the main disadvantage is the complexity of the design, which consists of a large number of sections; corona instability. RU: В работе проведен анализ наиболее распространенных электродных систем и конструкций аппаратов с вертикальными и горизонтальными электродами, дисковых и ленточных электроосадителей, электроосадителей с цилиндрическими и барабанными электродами, шнековыми электроосадителями и коронного электросепаратора для очистки масла в электрическом поле. Электроосадители с вертикальными и горизонтальными электродами в процессе работы нуждаются в периодической промывке электродной системы, что является их недостатком. К электроосадителям с пластинчатыми электродами относятся дисковые и ленточные электроосадители. Общим недостатком электроочистителей является возможность удаления только таких частиц примесей, имеющих заряд, к тому же только определенного знака. К существенным недостаткам барабанного аппарата следует отнести малую площадь поверхности осаждающего электрода. Шнековые осадители обладают хорошо организованным процессом очистки жидкости, однако основным недостатком является сравнительно малая поверхность электродов. Электродные системы коронного разряда позволяют получить поток ионов в газовой среде, однако основным недостатком является сложность конструкции.
Analysis of electrode systems and structures of appliances for purification of oils in the electric field
Анализ электродных систем и конструкций аппаратов для очистки масла в электрическом поле
Keywords: електричне поле; олія; очищення; електродні системи; апарати; конструкція; electric field; oil; cleaning; electrode systems; devices; construction; электрическое поле; растительное масло; очистка; электродные системы; аппараты; конструкция